NOx catalyzed pathway of stratospheric ozone depletion: a coupled cluster investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2012)
We report a theoretical investigation on the NOx catalyzed pathways of stratospheric ozone depletion using highly accurate coupled cluster methods. These catalytic reactions represent a great challenge to state-of-the-art ab initio methods, while their mechanisms remain unclear to both experimentalists and theoreticians. In this work, we have used the so-called ``gold standard of quantum chemistry,'' the CCSD(T) method, to identify the saddle points on NOx-based reaction pathways of ozone hole formation. Energies of the saddle points are calculated using the multireference variants of coupled cluster methods. The calculated activation energies and rate constants show good agreement with available experimental results. Tropospheric precursors to stratospheric NOx radicals have been identified, and their potential importance in stratospheric chemistry has been discussed. Our calculations resolve previous conflicts between ab initio and experimental results for a trans nitro peroxide intermediate, in the NOx catalyzed pathway of ozone depletion.

New scheme for perturbative triples correction to (0,1) sector of Fock space multi-reference coupled cluster method: Theory, implementation, and examples - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2015)
We propose a new elegant strategy to implement third order triples correction in the light of many-body perturbation theory to the Fock space multi-reference coupled cluster method for the ionization problem. The computational scaling as well as the storage requirement is of key concerns in any many-body calculations. Our proposed approach scales as N-6 does not require the storage of triples amplitudes and gives superior agreement over all the previous attempts made. This approach is capable of calculating multiple roots in a single calculation in contrast to the inclusion of perturbative triples in the equation of motion variant of the coupled cluster theory, where each root needs to be computed in a state-specific way and requires both the left and right state vectors together. The performance of the newly implemented scheme is tested by applying to methylene, boron nitride (B2N) anion, nitrogen, water, carbon monoxide, acetylene, formaldehyde, and thymine monomer, a DNA base. (C) 2015 AIP Publishing LLC.

Nuclear parity- and time-reversal-symmetry violation in the (HgH)-Hg-201 molecule - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2019)
Investigation of the nuclear magnetic quadrupole moment (MQM) is an excellent way to reveal the new physics in the hadron sector of matter. Therefore, we investigate the violation of parity (P) and time-reversal (T) invariance induced by the MQM of the( 201) Hg nucleus in the HgH molecule, which has been proposed as a very promising candidate for the experimental search of the electric dipole moment of electron [M. G. Kozlov and A. Derevianko, Phys. Rev. Lett. 97, 063001 (2006)]. We report the precise value of the molecular parameter, W-M, associated with the P, T-odd nuclear MQM-electron interaction in (HgH)-Hg-201 using the four-component relativistic coupled-cluster method. This parameter is required to interpret the experimental P, T-odd frequency shift in terms of the MQM of nuclei. Furthermore, the magnetic hyperfine structure (HFS) constants of the molecule are computed at the same level of theory. We also study the role of core-correlating functions and the virtual energy functions in the calculations of the HFS constant and W-M. The most reliable value of W(M )in HgH is obtained as 3.22 x 10 (33) Hz/e cm (2) with an uncertainty of around 6%.

Negative ion resonance states: the fock-space coupled-cluster way - Basumallick, Suhita; Sajeev, Y.; Pal, Sourav; Vaval, Nayana (Journal of Physical Chemistry A, 2020)
The negative ion resonance states, which are electron-molecule metastable compound states, play the most important role in free-electron controlled molecular reactions and low-energy free-electron-induced DNA damage. Their electronic structure is often only poorly described but crucial to an understanding of their reaction dynamics. One of the most important challenges to current electronic structure theory is the computation of negative ion resonance states. As a major step forward, coupled-cluster theories, which are well-known for their ability to produce the best approximate bound state electronic eigen solutions, are upgraded to offer the most accurate and effective approximations for negative ion resonance states. The existing Fock-space coupled-cluster (FSCC) and the equation-of-motion coupled-cluster (EOM-CC) approaches that compute bound states are redesigned for the direct and simultaneous determination of both the kinetic energy of the free electron at which the electron-molecule compound states are resonantly formed and the corresponding autodetachment decay rate of the electron from the metastable compound state. This Feature Article reviews the computation of negative ion resonances using the FSCC approach and, in passing, provides the highlights of the equivalent EOM-CC approach.